Artificial Intelligence (AI) Dalam Manajemen Farmasi dan Pelayanan Kefarmasian - Zakkiya Sabilla; Zahratul Humaidah; Elsa Tectona Zulianti; Renata Setya Agustin; Rizka Tri Amanda Hidayat; Namira Salsabillah; Firlia Nur Afifah; Alvan Andika Permadani; Rachma Hanifah (CV. ITTC INDONESIA, 2026)
The development of Artificial Intelligence (AI) has significantly transformed pharmaceutical services by improving efficiency, accuracy, and decision-making quality. This journal review aims to analyze the development of AI implementation in pharmacy services, compare research methods, and identify its benefits, limitations, and future opportunities. The method used was a Narrative Literature Review of ten scientific articles published between 2023 and 2026, collected from databases such as Google Scholar, PubMed, ScienceDirect, SpringerLink, and IEEE Xplore. The review found that AI technologies, including Machine Learning, Artificial Neural Networks, Natural Language Processing, Blockchain, Cloud Computing, and Predictive Analytics, can improve the accuracy of drug demand forecasting, reduce medication errors, optimize inventory management, and support clinical pharmacy services. However, most studies still focus on model development or simulations, so real-world implementation in pharmacy practice remains limited. Overall, AI has strong potential to support the digital transformation of pharmacy services, although further validation and readiness of human resources are still needed.